Interventional Nephrology: a new subspecialty of Nephrology - Efstratiadis, G (LITHOGRAPHIA Antoniadis I.-Psarras Th. G.P., 2007)
Interventional Nephrology is a new and emerging subspecialty of Nephrology that mainly deals with ultrasonography of kidneys and ultrasound-guided renal biopsy, insertion of peritoneal dialysis catheters, tunneled dialysis catheters as a vascular access for patients undergoing hemodialysis as well as percutaneous endovascular procedures performed to manage dysfunction of arteriovenous fistulas or grafts in end stage renal disease patients. Traditionally, these procedures have been delegated to a variety of specialists with resultant delays in diagnosis and initiation of therapy. To avoid the delays nephrologists have taken the initiative to perform these procedures themselves. Indeed, recent data have emphasized that nephrologists can safely and successfully perform these procedures with excellent results. The success of nephrologist’s role in Interventional Nephrology insures the ideal management of renal patients with effectiveness, safety and lower cost for Public Health System. Certainly nephrologists must have adequate training and develop the necessary skills in the new fields as a prerequisite for the success of the concept.